DETERMINAN MINAT WIRAUSAHA PADA MAHASISWA - Nida Nusaibatul Adawiyah; Mufid Suryani; Risa Septiani (Politeknik Bisnis Indonesia, 2022)
Global economic growth after the current pandemic is still quite good. Handling after the pandemic has seen a significant impact on Indonesia's economic recovery by strengthening the focus on job creation. One of the factors that influence the economic growth of a country is entrepreneurship. Entrepreneurship can create jobs through individuals who are involved in entrepreneurial activities, form new jobs by exploring high growth potential supported by technology. The purpose of this study is to analyze the factors that influence entrepreneurial interest in Gunadarma University students. The research method used is descriptive analysis using multiple linear regression with SPSS application. The results of this study indicate that partially self-efficacy, motivation and entrepreneurial education variables have a positive effect on entrepreneurial interest. Based on the results of the simultaneous test, the variables of self-efficacy, motivation and entrepreneurship education together have a significant effect on entrepreneurial interest.